2014
DOI: 10.1007/s00198-014-2752-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zoledronic acid treatment in Paget disease of bone

Abstract: We recommend zoledronic acid in the first-line treatment of Paget disease of bone in achieving and maintaining remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Bisphosphonates are widely used as a first‐line treatment for osteoporosis (Grey & Reid, ), preventing bone fracture. Additionally, bisphosphonates have been exploited for their antiproliferative and pro‐apoptotic effects on tumor cells and have been used for the treatment of Paget's disease, breast cancer, bone metastasis, multiple myeloma, and primary hyperparathyroidism (Baykan et al., ; Khan, Grey, & Shoback, ; Pavlakis, Schmidt, & Stockler, ). As the prevalence of osteoporosis has increased, the number of patients suffering from bisphosphonate‐associated osteonecrosis of the jaw (BRONJ) has also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates are widely used as a first‐line treatment for osteoporosis (Grey & Reid, ), preventing bone fracture. Additionally, bisphosphonates have been exploited for their antiproliferative and pro‐apoptotic effects on tumor cells and have been used for the treatment of Paget's disease, breast cancer, bone metastasis, multiple myeloma, and primary hyperparathyroidism (Baykan et al., ; Khan, Grey, & Shoback, ; Pavlakis, Schmidt, & Stockler, ). As the prevalence of osteoporosis has increased, the number of patients suffering from bisphosphonate‐associated osteonecrosis of the jaw (BRONJ) has also increased.…”
Section: Discussionmentioning
confidence: 99%
“…in their retrospective study of 12 patients showed that remission occurred at 6 months and was sustained till 18 months following a single dose of intravenous ZA. [14] Tucci studied the effect of ZA in 14 patients with PDB who had previously received other BPs but had either failed to achieve remission or to maintain it for more than 12 months. Treatment with ZA resulted in remission in 13 out of 14 patients, lasting from 12 to 60 months.…”
Section: Discussionmentioning
confidence: 99%
“…Пред-почтение в терапии заболевания отдается бисфосфонатам в силу их избирательного действия на костную ткань и длительного сохранения стойкого эффекта [28][29][30][31][32]. Таким образом, двукрат-ное введение золедроновой кис-лоты пациентке с КБП позво-лило достичь низкого уровня активности заболевания, что согласуется с данными других авторов [33][34][35][36], и провести артропластику тазобедренного сустава. Врачам, работающим с костной патологией, надо знать об этом заболевании вви-ду его высокой распространен-ности, поскольку своевремен-ная терапия позволяет избежать прогрессирования болезни, раз-вития ее осложнений и потреб-ности в высокотехнологичной медицинской помощи.…”
Section: пациент а 49 лет в 2004 г (в возрасте 37 лет) по-явилисьunclassified